CONDITIONS FOR THE IMPLEMENTATION OF THE FOOD SAFETY MANAGEMENT SYSTEM (HACCP) IN UKRAINE: ADMINISTRATIVE AND LEGAL ASPECT - Усенко, Олексій Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to explore the regulatory bases for the implementation of the Hazard Analysis and Critical Control Points (HACCP) system in Ukraine as a factor in food safety. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: generalized requirements for the development, implementation and application of permanent procedures based on the principles of the Food Safety Management System (HACCP). Discussion: clarified the provisions on the introduction of prerequisites by market operators, the principles of the HACCP, the development of permanent monitoring procedures, a simplified approach to the application of the HACCP system for certain market operators, etc. Requirements for safety and quality of food products were considered to be of particular relevance at all times, because non-compliance with these requirements could be detrimental to human life and health. Food safety is one of the main areas that determines the health of the population, preservation of the gene pool of the nation. At the same time, the decision of these issues is related not only to the quality control of the final product, but also to the monitoring of production processes throughout the production chain for the timely detection of hazardous products. This monitoring system was called Hazard Analysis and Critical Control Points (HACCP) - a system that identifies, assesses and controls the hazards that are critical to the safety of food products. The EU considers HACCP to be the most effective method of ensuring food safety and requires all food industry enterprises to implement, observe and implement procedures based on the principles of HACCP. The principles of the HACCP, the program-preconditions of the HACCP system, the sequence of the development of the HACCP system, are formalized in accordance with the Requirements for the development, implementation and application of permanent procedures based on the principles of the Food Safety Management System (HACCP) (from 01.10.2012 № 590). The analysis is of practical importance for the practical implementation of the procedures reviewed in order to ensure the safety of food products. The direction of further research is the details of the programs, the prerequisites for each of the predicted components, as well as the procedures that ensure the efficient functioning of the HACCP system.